PENYULUHAN BUDIDAYA RUMPUT LAUT DALAM PENGEMBANGAN EKONOMI MASYARAKAT PESISIR KELURAHAN LOWU-LOWU KECAMATAN LEALEA KOTA BAUBAU - TARNO; ISMAIL FAILU; SAFRIN EDY; ARDY LESTARY AWALUDDIN RASYID (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2019)
Kappaphycus alvarezii seaweed is one of the main commodities of cultivated fisheries which is widely cultivated because its production technology is relatively cheap and easy and post-harvest handling is relatively easy and simple. This type of seaweed is capable of producing carrageenan which is widely used in various industries. Kappaphycus alvarezii seaweed is one of the main commodities of cultivated fisheries which is widely cultivated because its production technology is relatively cheap and easy and post-harvest handling is relatively easy and simple. This type of seaweed is capable of producing carrageenan which is widely used in various industries. The main targets to be achieved include: (1) increasing the income of partner groups through fishing activities; (2) increasing production of partner groups through technical guidance for seaweed cultivation; (3) increasing business productivity through production and business management development; (4) application of bookkeeping by recording all business activities and expenses incurred; (5) journal publication Counseling was held from October to November 2019 in Lowu-Lowu Waters, Buabau City, Southeast Sulawesi Province. The meeting was attended by group members, fishery extension workers and the secretary of the Lowu-Lowu village. People Participants totaled 30